Stars over sunset boulevard ebook - Meissner, Susan (2016)
In this novel from the acclaimed author of A Bridge Across the Ocean and The Last Year of the War , two women working in Hollywood during its Golden Age discover the joy and heartbreak of true friendship. Los Angeles, Present Day . When an iconic hat worn by Scarlett O’Hara in Gone With the Wind  ends up in Christine McAllister’s vintage clothing boutique by mistake, her efforts to return it to its owner take her on a journey more enchanting than any classic movie.... Los Angeles, 1938 . Violet Mayfield sets out to reinvent herself in Hollywood after her dream of becoming a wife and mother falls apart, and lands a job on the film-set of Gone With the Wind . There, she meets enigmatic Audrey Duvall, a once-rising film star who is now a fellow secretary. Audrey’s zest for life and their adventures together among Hollywood’s glitterati enthrall Violet...until each woman’s deepest desires collide.   What Audrey and Violet are willing to risk, for themselves and for each other, to ensure their own happy endings will shape their friendship, and their lives, far into the future.  CONVERSATION GUIDE INCLUDED